An inscribed and sculpted Hero stone (Memorial stone) - Temples of India Project Team (Jio Institute, 2024)
Seen here is an inscribed and sculpted hero stone (memorial stone) in the Suswani Mata temple premises, which is built in memory of the deceased soul. It is approximately five feet in height and the front face has an inscription at the centre and human figures in the upper part. The stele is capped with a shikhara (superstructure or spire) motif.